2015
DOI: 10.1097/qai.0000000000000588
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Treatment Is Associated With Iron Deficiency in HIV-Infected Malawian Women That Is Mitigated With Supplementation, but Is Not Associated With Infant Iron Deficiency During 24 Weeks of Exclusive Breastfeeding

Abstract: Objective In resource-limited settings without safe alternatives to breastfeeding, the WHO recommends exclusive breastfeeding and antiretroviral (ARV) prophylaxis. Given the high prevalence of anemia among HIV-infected women, mothers and their infants (via fetal iron accretion) may be at risk of iron deficiency. We assessed the effects of maternal micronutrient-fortified lipid-based nutrient supplements (LNS) and maternal ARV treatment or infant ARV prophylaxis on maternal and infant iron status during exclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
(85 reference statements)
1
7
0
1
Order By: Relevance
“…TfR can be elevated when there is iron-deficient erythropoiesis or tissue iron deficiency without anemia (53), which may be more common in people with chronic diseases and inflammation (54). The results on ferritin, TfR, and hemoglobin reported here confirm our earlier findings from a smaller, matched mother-infant subsample of BAN study participants (55).…”
Section: Discussionsupporting
confidence: 93%
“…TfR can be elevated when there is iron-deficient erythropoiesis or tissue iron deficiency without anemia (53), which may be more common in people with chronic diseases and inflammation (54). The results on ferritin, TfR, and hemoglobin reported here confirm our earlier findings from a smaller, matched mother-infant subsample of BAN study participants (55).…”
Section: Discussionsupporting
confidence: 93%
“…6 Values across all prenatal visits. 7 Participants reported previous displacement during the conflict in Northern Uganda area that ended in 2006 (participant enrollment started in October 2012). 8 Data were available for 241 women.…”
Section: Resultsmentioning
confidence: 99%
“…It is also recommended that antiretroviral therapy (ART) 11 should be initiated for anyone who is living with HIV and should be continued for life (3). However, some ART regimens may propagate weight loss and concomitant shifts in body composition (4,5) and adversely affect micronutrient status (6)(7)(8). These deficits can be exacerbated during periods of higher nutritional needs such as lactation.…”
Section: Introductionmentioning
confidence: 99%
“…The same supplement slowed postpartum weight loss among HIV positive women (Kayira et al, ). The Breastfeeding, Antiretrovirals, and Nutrition Study in Malawi likewise found that postnatal lipid‐nutrient supplement prevented iron depletion in women using antiretrovirals (Widen et al, ). In the iLiNS‐DYAD study in Ghana, low‐calorie lipid‐nutrient supplements reduced maternal anemia, increased hemoglobin, and decreased iron deficiency (Adu‐Afarwuah et al, ), and younger women finished pregnancy with lower cortisol levels if they consumed lipid‐nutrient supplements relative to multiple micronutrients (Oaks et al, ).…”
Section: Prenatal Supplementation Studies: Contingent Outcomesmentioning
confidence: 99%